Blockchain-Enhanced Vehicular Ad-hoc Networks (B-VANETs): Decentralized Traffic Coordination and Anonymized Communication - Sadineni, Giribabu; Singh, Jaibir; Rani, Suman; Rao, Goda Srinivasa; Pasha, M. Jahir; Lavanya, Addepalli (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The research systematically evaluates an intelligent transportation system, specifically focusing on Blockchain-based Vehicular Ad Hoc Networks (B-VANETs) through simulations encompassing decentralized traffic coordination, anonymized communication, and data encryption. Employing a detailed methodology, including blockchain simulations and trust score monitoring, the simulations unveil diverse vehicle behaviors in traffic scenarios, highlighting the need to balance acceleration and deceleration. Communication dynamics among autonomous vehicles in B-VANETs vary, emphasizing the importance of optimizing communication strategies. Trust scores evolve dynamically, illustrating the complex nature of trust management within autonomous systems operating in B-VANETs. Six simulations with thoughtfully chosen parameters provide robust data while maintaining computational efficiency. Comparative analysis reveals stable trust scores and traffic coordination, with an average trust score of approximately 1.411, and the system demonstrates computational efficiency, with runtime variations between 1.363 and 1.540 seconds.